Echocardiographic Parameters to Predict Atrial Fibrillation in Clinical Routine—The EAHsy-AF Risk Score - Sieweke, Jan-Thorben; Hagemus, Jan; Biber, Saskia; Berliner, Dominik; Grosse, Gerrit M.; Schallhorn, Sven; Pfeffer, Tobias Jonathan; Derda, Anselm A.; Neuser, Jonas; Bauersachs, Johann; Bavendiek, Udo (Frontiers in Cardiovascular Medicine, 2022)
Background Echocardiographic parameters representing impaired left atrial (LA) function and remodeling are of high value to predict atrial fibrillation (AF). This study aimed to develop a prediction model for AF easily to apply in clinical routine containing echocardiographic parameters associated with LA remodeling and—function. Methods and Results This monocentric, semi-blinded, controlled analysis included 235 patients to derive a prediction model. This prediction model was tested in a validation cohort encompassing 290 cardiovascular inpatients. The derivation and validation cohort included 54 (23%) and 66 (23%) patients with AF, respectively. Transthoracic echocardiography, comprising parameters indicating left atrial remodeling [septal/lateral total atrial conduction time (s/l PA-TDI)] and left atrial volume indexed to a' (LAVI/a') was performed in each patient. Based on multivariable regressions analysis, four variables were enclosed into the EAHsy (Echocardiography, Age, Hypertension)-AF risk score for AF prediction: Hypertension, Age, LAVI/a‘ and septal PA-TDI. In the validation cohort discrimination was strong (C-statistic 0.987, 95%CI 0.974–0.991) with an adequately performed calibration. The EAHsy-AF risk score was associated with a more precise prediction of AF in comparison to commonly used AF-scores (CHADS2-, ATLAS-, ARIC-, CHARGE-AF score). Conclusion The EAHsy-AF-Score containing age, hypertension and echocardiographic parameters of atrial dysfunction and remodeling precisely predicts the incidence of AF in a general population of patients with cardiovascular disease. The EAHsy-AF risk score may enable more selective rhythm monitoring in specific patients at high risk for AF.